2008
DOI: 10.1186/1744-8069-4-16
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.7 Expression is Increased in Painful Human Dental Pulp

Abstract: Background: Animal studies and a few human studies have shown a change in sodium channel (NaCh) expression after inflammatory lesions, and this change is implicated in the generation of pain states. We are using the extracted human tooth as a model system to study peripheral pain mechanisms and here examine the expression of the Na v 1.7 NaCh isoform in normal and painful samples. Pulpal sections were labeled with antibodies against: 1) Na v 1.7, N52 and PGP9.5, and 2) Na v 1.7, caspr (a paranodal protein used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 44 publications
6
38
0
Order By: Relevance
“…In the dental clinic, the topical application or subcutaneous administration of methyl eugenol provides a means to produce a high concentration of the drug at a localized site for a certain period. Furthermore, a recent study has demonstrated an increased Na v 1.7 expression in painful human dental pulp [26] . Therefore, given the inhibition of recovery by methyl eugenol, we propose that methyl eugenol could be a more effective analgesic for the treatment of toothache than clove oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the dental clinic, the topical application or subcutaneous administration of methyl eugenol provides a means to produce a high concentration of the drug at a localized site for a certain period. Furthermore, a recent study has demonstrated an increased Na v 1.7 expression in painful human dental pulp [26] . Therefore, given the inhibition of recovery by methyl eugenol, we propose that methyl eugenol could be a more effective analgesic for the treatment of toothache than clove oil.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Na v 1.7 in propagating pain information has been strongly indicated by the fact that a Na v 1.7 congenital channelopathy results in the inability to experience pain [23][24][25] . Recently, a study demonstrated an increase in Na v 1.7 expression in painful human dental pulp [26] . Based on the antinociceptive and anesthetic actions of methyl eugenol in vivo and of Xixin in dental clinics, the peripheral TTX-sensitive channel isoform, Na v 1.7, represents a good candidate for the channel involved in the effects of methyl eugenol.…”
Section: Many Biological Actions Of Methyl Eugenol Have Been Reportedmentioning
confidence: 99%
“…Despite their well-established roles in nociception, the mechanisms by which Na v 1.7 and Na v 1.8 isoforms specifically contribute to neuropathic pain are still under debate. On the one hand, knocking down Na v 1.8 prevents neuropathic pain in mice (40), Na v 1.7 accumulates in human painful dental pulp (15), and gain-of-function mutations of Na v 1.7 and Na v 1.8 are linked to exaggerated pain in humans (12,13). A recent simulation study suggested that Na v 1.7 and Na v 1.8 may act synergistically to increase the amplitude of subthreshold oscillations and increase the frequency of repetitive firing in the periphery (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Na v 1.7 and Na v 1.8 gain-offunction mutations in painful peripheral neuropathy syndromes were recently described (12,13). Not only are Na v 1.7 and Na v 1.8 important in inherited pain disorders, but also in acquired pain disorders, where their increased expression has already been linked to diverse chronic pain symptoms (14)(15)(16). Studies using knockout mice have implicated Na v 1.7 and Na v 1.8 in acute and inflammatory pain (17)(18)(19)(20), but their involvement in hyperexcitability and neuropathic pain remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that among the 9 subtypes of Nav channels in humans, Nav1.8 can generate an electrical impulse and is involved in the transmission of nociceptive information under cold conditions and plays a crucial role in pain perception at a low temperature (14), our finding supports the notion that Nav1.8 is involved in the conduction of TRPA1-mediated cold nociception in human dental pulp. The TRPA1+ axons in the dental pulp that do not express Nav1.8 may express other Navs, possibly Nav1.7 or Nav1.9, both of which have been shown to be overexpressed after pulpal inflammation and have been implicated in the perception of pain after inflammation and nerve injury (30)(31)(32). …”
Section: Discussionmentioning
confidence: 99%